Family firms, employee satisfaction, and corporate performance - Huang, Minjie; Li, Pingshu; Meschke, Felix; Guthrie, James P. (Journal of Corporate Finance, 2015)
Prior research shows that family control affects firm value through capital investment, debt financing, M&A activities, and governance structure. This study investigates the role of corporate culture in family firms and its implications for firm value. We use more than 100,000 surveys collected by Glassdoor between 2008 and 2012 that capture how employees perceive their company's culture. We find that employees who work for firms with active founders rate their companies higher than employees in nonfamily firms, especially if the founder runs the company. In contrast, employee satisfaction in scion firms does not differ from nonfamily firms, and when scions run the company, employees are less satisfied. Scion firms also exhibit significant lower employee satisfaction during the recent financial crisis. Furthermore, employee assessments predict subsequent firm performance measured by Tobin's q and return on assets (ROA). Our findings provide evidence that family firms exhibit a human-capital-enhancing culture that improves firm performance.